A rational diagnostic approach to the "phantom hCG" and other clinical scenarios in which a patient is thought to be pregnant but is not - Oluwafunmilayo Oyatogun; Mandeep Sandhu; Stephanie Barata-Kirby; Erin Tuller; Danny J. Schust (SAGE Publishing, 2021)
The scenario in which a patient tests positive for human chorionic gonadotropin (hCG) in the absence of pregnancy can pose a diagnostic dilemma for clinicians. The term "phantom hCG" refers to persistently positive hCG levels on diagnostic testing in a nonpregnant patient and such results often lead to a false diagnosis of malignancy and subsequent inappropriate treatment with chemotherapy or hysterectomy. There remains a need for a consistent and rational diagnostic approach to the "phantom hCG." This article aims to review the different etiologies of positive serum hCG testing in nonpregnant subjects and concludes with a practical, stepwise diagnostic approach to assist clinicians encountering this clinical dilemma.